Building security rating system : checklists to assess risks, consequences, and security countermeasures - Ettouney, Mohammed (American Society of Civil Engineers, 2015)
Prepared by the Building Rating Security Committee (BRSC) of the Architectural Engineering Institute of ASCE. This Manual of Practice presents a building security rating system (BSRS) that can be used to improve the security of buildings and occupants subjected to violent attack. The BSRS offers a comprehensive method to account for threats and hazards, consequences and impacts, and vulnerability and mitigation as related to building security. In doing so, it provides a quantifiable measure of building security status. Multidisciplinary in scope, the BSRS uses a rigorous risk-based system that first identifies physical and operational criteria that enhance building security and then evaluates the extent to which a building meets these criteria. The BSRS has three elements: building classification, security countermeasures, and a rating system. MOP 128 presents the risk-based tools for classifying a building by its hazards and consequences, as well as identifying vulnerabilities to be addressed with security countermeasures. The rating system designates a building.s security level in five categories: rated, bronze, silver, gold, and platinum. Appendixes present extensive commentary on the factors for building classification and security countermeasures for each level of the rating system. Ten years in development, the BSRS is now publicly available for the first time. Architects, designers, structural engineers, planners, building owners, security professionals, and government officials will rely on MOP 128 as the essential reference for implementing improved, cost-effective building security.
Keywords: Buildings -- Security measures -- Evaluation.; Security systems -- Evaluation.; elektronické knihy; electronic books